MENINGKATKAN AKTIVITAS DAN KETERAMPILAN BERPIKIR KRITIS PADA ASPEK KOGNITIF ANAK MELALUI MODEL MERAK - Rahmah, Mutia; Amelia, Rizky (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
This research is based on the low activity of children and critical thinking skills in the cognitive aspect of knowing the concepts of many and little. The solution to solve this problem is to use the MERAK model which is a combination of the problem based learning, make a match, and badaku media model. The purpose of this study is to analyze teacher activities, children's activities, children's critical thinking skills, and the results of cognitive development in knowing the concepts of many and little. The approach used is a qualitative approach and a type of Class Action Research (CAR) with 4 meetings. Data analysis showed that teachers' activities reached a percentage of 97% with the criterion of